Graphene: A future science material for water treatment - Suhail, Mohammad (European Journal of Chemistry, 2022)
Graphene is showing its versatility continuously by playing the most important role in many fields of science. Water treatment is one of them. In the present scenario, the supply of the safe and pure water has become the main priority. Especially, the most denser and populated areas are demanding of it. Although water treatment is done by applying different methods using different materials, no material showed the results as good as graphene-based materials. The current article deliberates not only the main properties of graphene but also their importance in the treatment of water. Besides, the current review also pronounces the method of graphene separation from the water after use and recycling. Efforts are made to discuss the role of graphene materials in the treatment of water. Henceforward, this article will definitely be very helpful for researchers, academicians, and administration authorities who are planning and developing new strategies for the removal of ionic as well as organic impurities from water.